2015
DOI: 10.5455/gmj-30-178278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the attitudes of general dental practitioners in Gaziantep about endodontics

Abstract: The purpose of this study is to determine the level of knowledge of dentists working in Gaziantep about the stages of root canal treatment. Questionnaires were reached to 118 general dental practitioners working in Gaziantep. Questionnaire was including questions such as age, gender, year of graduation, root canal medicament, root canal sealer, irrigation solution, use of rotary instrument and apex locator, number of sessions, indication of retreatment. Results were analyzed with chi-square test. A hundred of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In one study, it was reported that in the Gaziantep city of Turkey, dentists working in private clinics performed more retreatments than those working in the public sector (15). The possible reason for this may be not being able to perform retreatment under high level of patient inflow in public sector.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, it was reported that in the Gaziantep city of Turkey, dentists working in private clinics performed more retreatments than those working in the public sector (15). The possible reason for this may be not being able to perform retreatment under high level of patient inflow in public sector.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was reported that 94% of endodontists in Brazil used electronic apex locator for working length detection (16). For Turkey, research has found that 42% of dentists relied on the method of determining working length with finger sensitivity (15) and 47.9% of dentists used radiography and electronic apex locators together in determining working length (16). The practitioners who participated in our study used the following methods for detecting working length: 18% radiography, 32% electronic apex locator, 7% hand sensitivity, and 43% radiography and electronic apex locator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation